Quality education as a sustainable development goal in the context of marginalized communities at the local level: a case study in Cluj-Napoca (Romania) - Pachiu, Ana-Maria Daniela; Mureşan, Gabriela-Alina; Man, Titus Cristian (Frontiers in Education, 2025)
This study focuses on SDG 4, “Quality Education,” as part of the 2030 Agenda for Sustainable Development, with a specific emphasis on the educational challenges faced by a marginalized community in the city of Cluj-Napoca (Romania). The research aims to capture perceptions both within and outside of this community. For this, we first gathered opinions and needs through face-to-face interviews in the community. To address educational inequalities, the study also examines the city’s population’s awareness, tolerance, and receptivity toward integrating students from disadvantaged backgrounds. This was assessed using online questionnaires, which were statistically validated by correlating response content with quantitative data. Our results found that, generally, the people of Cluj-Napoca are tolerant and very tolerant toward students from the marginalized community. The study further analyzes the key factors affecting the education of children in the disadvantaged community and suggests solutions based on the collected insights for relevant authorities.